2020
DOI: 10.1027/0227-5910/a000616
|View full text |Cite
|
Sign up to set email alerts
|

A Community-Based Response to a Suicide Cluster

Abstract: Abstract. Background: A 45-month community-based suicide prevention program was launched in response to the emergence of a suicide cluster in 2010 in Hong Kong. Aims: This study aimed to evaluate the effectiveness of the program, document the implementation and outcomes of the project, and identify factors that contribute to the outcomes. Method: The program was delivered following the five key components of the public health approach: (a) community consensus building; (b) surveillance and monitoring; (c) deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…The present findings contribute to empirical knowledge toward formulating effective interventions for youth suicide prevention. Apart from standard means, such as restriction of access to means of suicide and responsible media reporting of suicide cases, other potential strategies include improved access to mental health care via a 24-h online emotional support system and promotion of suicide prevention programs that are community based [ 64 ] or distance based [ 65 ]. Siu [ 66 ] has advocated earlier prevention strategies, such as online monitoring programs and life skills training programs, for the adolescents to help with their transition into young adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…The present findings contribute to empirical knowledge toward formulating effective interventions for youth suicide prevention. Apart from standard means, such as restriction of access to means of suicide and responsible media reporting of suicide cases, other potential strategies include improved access to mental health care via a 24-h online emotional support system and promotion of suicide prevention programs that are community based [ 64 ] or distance based [ 65 ]. Siu [ 66 ] has advocated earlier prevention strategies, such as online monitoring programs and life skills training programs, for the adolescents to help with their transition into young adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, 51 college employees who engaged in ASIST demonstrated significant improvements in responding to people in distress when compared to a control group 39 . Both Asarnow and Wang 40 and Lai et al 41 found that community engagement in suicide prevention programs resulted in significant decreases in suicides in the United States and Hong Kong, respectively. Considering the positive effects of such programs, it is recommended that communities promote some form of suicide and self‐harm education or training.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of jumping might be explained by its accessibility and lethality given that HK is the world’s densest city, where most people live in multistory buildings. Installing barriers such as platform screen doors have been found to be effective suicide prevention strategies in HK railway stations, thus adopting similar community-based suicide prevention approaches for high-rise buildings may be similarly effective (Lai et al, 2020 ; Law et al, 2009 ). Experiences of restricting access of a suicidal person to charcoal or displaying warning labels on charcoal packs appear to have been another effective suicide prevention model in the community (Wu et al, 2012 ; Yip et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%